1990
DOI: 10.1136/oem.47.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges in human lymphocytes treated with silica.

Abstract: The abilities of Min U Sil quartz or tridymite particles to induce sister chromatid exchanges (SCEs) in cultures of human lymphocytes plus monocytes or of human purified lymphocytes were investigated. With cultures of lymphocytes plus monocytes the level of SCEs was significantly enhanced after treatment with tridymite at the highest dose tested (50 micrograms/cm2). No effect was observed with purified lymphocytes. Quartz did not give clear cut results. Complementary experiments with tridymite filtrates sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…However, silica has also recently been shown to generate free radicals detectable by electron spin resonance (ESR) spectroscopy under a variety of experimental conditions (16)(17)(18). It was proposed that these free radicals play an important role in the mechanism of silica toxicity and carcinogenicity (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…However, silica has also recently been shown to generate free radicals detectable by electron spin resonance (ESR) spectroscopy under a variety of experimental conditions (16)(17)(18). It was proposed that these free radicals play an important role in the mechanism of silica toxicity and carcinogenicity (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Tridymite induced a significant number of sister chromatid exchanges (SCEs) in co-cultures of human lymphocytes and monocytes (P<0.05 compared with control cells) at doses of 5 and 50 µg/cm 2 (87.9% of the tridymite particles had a diameter <1 µm). However, the number of SCEs in purified human lymphocytes that were treated with the same doses of tridymite particles did not differ significantly from control cells [Pairon et al 1990]. Results of the same experiments with quartz did not yield a clear conclusion about the ability of quartz to induce a significant number of SCEs (Table 21) [Pairon et al 1990].…”
Section: Genotoxicity and Related Effectsmentioning
confidence: 88%
“…However, the number of SCEs in purified human lymphocytes that were treated with the same doses of tridymite particles did not differ significantly from control cells [Pairon et al 1990]. Results of the same experiments with quartz did not yield a clear conclusion about the ability of quartz to induce a significant number of SCEs (Table 21) [Pairon et al 1990]. …”
Section: Genotoxicity and Related Effectsmentioning
confidence: 88%
See 1 more Smart Citation
“…Kaolin is used in paper production, in paints, rubber, plastic, ceramic, chemical, pharmaceutical and cosmetic industries 1 . Pairon et al (15) in 1990 studied the interaction of Kaolin with cell lines and found a variety of membrane interactions and metabolic impairments. Kaolin in the recent past has been of interest in clinical studies due to its role in achieving haemostasis in Oculoplastic Surgery as a local application (16) or intra-abdominal surgery with Kaolin impregnated gauze as a leave-in substance for rapid hemorrhage control in critically injured patients in combat (17).…”
Section: Discussionmentioning
confidence: 99%